Technology for access to text and graphics for people with visual impairments and blindness in vocational settings. - Strobel W; Fossa J; Arthanat S; Brace J (Journal of Vocational Rehabilitation, 2006)
The unemployment rate of people with disabilities has long been out of proportion to the general community despite federal goals and mandates to ameliorate the problem. A consistent issue is the access and knowledge related to accommodations. The need for accommodations for specific disability groups will vary according to the functional limitations presented by the disability. For instance, the accommodation needs for an individual with a significant physical disability will be very different than what one might need for a sensory disability such as hearing or vision loss. This paper will focus on the need for accommodation and emerging technologies in the employment of people with visual impairments.